Reinterpretasi Makna Budaya Sungkem Sebagai Ajaran Budi Pekerti Dalam Sloka Sarasamuccaya - A. A. Kade Sri Yudari; Ni Wayan Karmini; Desak Nyoman Seniwati (Jayapangus Press, 2022)
Bali’s an island that’s closely related to various local wisdoms including the procedures for behavings including through sungkem. The values of hospitality and morality in tradition are characteristic of culture the archipelago. The concept of sungkem Hinduism means respect for the catur guru. In everyday life it’s implemented as a tradition that a noble meaning but is now rarely applied, especially in Bali. This research aims to examine and reinterpret the meaning of sungkem as the application of the teachings character as stated in the Sarasamuccaya Sloka. Writing research using qualitative methods with descriptive-interpretative exposure techniques. Through the paradigm of social behavior, supported by a literary anthropological approach as an analytical tool, it shows a more transparent description of the object in a narrative manner. The results of the study found that the sungkem tradition research carried out in the Sugeng Wiyosan ritual at the Mancawarna Palace has an implementation meaning as an ethical teaching for millennial youth who are allegedly prone to moral degradation. The Sungkem culture is also an effort to protect the environment and strengthen family ties. By reviving and preserving ancestral traditions full of positive values, it can shape the character and maintain the dignity of the younger generation from an early age as mentioned in several verses of the Sarasamuccaya Sloka. Recommendations adrresed to the wider community regarding the internalization of the meaning of mutual respect among God’s creature as Tri Hita Karana should always be echoed both individually and in groups to prevent exposure to the negative currents of globalization among young people.